Comparison Analysis of CBR Value Enhancement of Soil Type in Swamp Area by Addition of Fly Ash - Indrayani Indrayani; Andi Herius; Arfan Hasan; Ahmad Mirza (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Roads was built on swamp areas should be consider the condition of the base soil, since the characteristics of the soil in swamp areas have always inundated and have a low soil carrying capacity (Subagyo, 2006). One of effort that could be done to improve the existing soil condition was used fly ash as a material for soil stabilization (Indera et al, 2016; Mina et al, 2016). This study was conducted to analyze the enhancement of CBR value on various soil types in swamp area by the addition of fly ash. Testing on the values of index properties, compaction, and CBR values was done in laboratory base on ASTM and AASHTO standars. The test results show that the type of soil at the location of the sampling is silty or clay gravel and sand, clay soil, and silty soil. The reduction of optimum water content after the addition of fly ash is the highest decrease of 20.92%. While the highest increase of dry content weight after the addition of fly ash was 0.904 gr / cm3. An enhancement in the value of CBR by the addition of 20% fly ash in the study area, however the increase magnitude depends on the existing soil types, ie 7.99% in the silty or clay gravel and sand, 6 - 8% in the clay soil and 0,22 - 5% on silty soil. This indicates that the addition of fly ash was the optimum used on the type of clay soil.